Proteinase inhibitors I and II from potatoes block UVB-induced AP-1 activity by regulating the AP-1 protein compositional patterns in JB6 cells - Liu, Guangming (The National Academy of Sciences, 2001)
Proteinase inhibitor I (Inh I) and proteinase inhibitor II (Inh II) from potato tubers are effective proteinase inhibitors of chymotrypsin and trypsin. Inh I and Inh II were shown to suppress irradiation-induced transformation in mouse embryo fibroblasts suggesting that they possess anticarcinogenic characteristics. We have previously demonstrated that Inh I and Inh II could effectively block UV irradiation-induced activation of transcription activator protein 1 (AP-1) in mouse JB6 epidermal cells, which mechanistically may explain their anticarcinogenic actions. In the present study, we investigated the effects of Inh I and Inh II on the expression and composition pattern of the AP-1 complex following stimulation by UV B (UVB) irradiation in the JB6 model. We found that Inh I and Inh II specifically inhibited UVB-induced AP-1, but not NFκB, activity in JB6 cells. Both Inh I and Inh II up-regulated AP-1 constituent proteins, JunD and Fra-2, and suppressed c-Jun and c-Fos expression and composition in bound AP-1 in response to UVB stimulation. This regulation of the AP-1 protein compositional pattern in response to Inh I or Inh II may be critical for the inhibition of UVB-induced AP-1 activity by these agents found in potatoes.